2016
DOI: 10.32607/20758251-2016-8-2-75-78
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress-Induced DNA Damage

Abstract: Although the heat-stress response has been extensively studied for decades, very little is known about its effects on nucleic acids and nucleic acid-associated processes. This is due to the fact that the research has focused on the study of heat shock proteins and factors (HSPs and HSFs), their involvement in the regulation of transcription, protein homeostasis, etc. Recently, there has been some progress in the study of heat stress effects on DNA integrity. In this review, we summarize and discuss well-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 49 publications
5
77
0
Order By: Relevance
“…This plesiomorphic form is made up of microscopic filaments known as protonema that are formed by chains of haploid cells 49 . A number of studies have shown that Physcomitrella efficiently renders homologous recombination-based error-free DNA damage repair, an attribute that is likely to confer adaptive advantage in high-temperature habitats that are generally associated with higher rates of DNA damage 73 . Together with a plausible vegetative/asexual lifestyle, error-free DNA damage repair capabilities can act to reduce genetic variability in Physcomitrella and, ultimately, slow down evolution via conservation of genomes 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…This plesiomorphic form is made up of microscopic filaments known as protonema that are formed by chains of haploid cells 49 . A number of studies have shown that Physcomitrella efficiently renders homologous recombination-based error-free DNA damage repair, an attribute that is likely to confer adaptive advantage in high-temperature habitats that are generally associated with higher rates of DNA damage 73 . Together with a plausible vegetative/asexual lifestyle, error-free DNA damage repair capabilities can act to reduce genetic variability in Physcomitrella and, ultimately, slow down evolution via conservation of genomes 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress could induce DNA break and inhibit DNA replication. [26] Caspase-3 might be involved in the increased DNA damage observed in animal skeletal muscles. [27] The caspase-3 activity in SJBW first increased and then decreased over time in low-temperature treatment (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sources of stress such as extreme heat or cold, hypoxia, and oxidative stress have been shown to cause DNA damage in human cells [Gregory and Milner, 1994;Gafter-Gvili et al, 2013;Luoto et al, 2013;Neutelings et al, 2013;Kantidze et al, 2016]. These stresses have also been shown to cause mutagenesis at trinucleotide repeats, which are implicated in the development of neurodegenerative disorders via the alt-NHEJ DNA repair pathway [Chatterjee et al, 2015[Chatterjee et al, , 2016b.…”
Section: Environmental Stressesmentioning
confidence: 99%